Novos tempos, velhos problemas: legislação sobre a questão social na primeira república - Covolan, Fernanda Cristina (2019)
The subject of this research proposed to think historically Brazilian social law in parallel to other countries in which there was similar initial structure. Within this theme, the main interest was to compare the Bismarckian German Welfare State and the historical circumscription of the social laws created in the First Republic, and the position of the jurists. In this sense, the main theoretical references were the political scientists specialized in the theme Esping-Andersen and Maurizio Ferrera; and the historians of Law Michael Stolleis and François Ewald. In documentary analysis, it was desired to take into account the existence of structures of slow and almost imperceptible historical movement in parallel with conjunctions that exert more intense forces, in conflict. In the first chapter, studying the reference points on Welfare State mentioned above, it was possible to observe that the Bismarckian model was characterized by conservatism, control of the class struggle, emphasis on character and moral construction, recognition of rights that maintained occupational differences, as from the existing forms of assistance and changes in legal forms and concepts. Thereafter, through historiographic sources and primary sources, the economic, political and social aspects related to the Brazilian social question in the First Republic were analyzed, and it was possible to verify that that the liberalism and the laissez-faire were constituted more in dominant discourse than in a real practice beginning in 1914, when internal and external material conjuncture pressured the modes of life and the actors involved. Finally, in the analysis of the formulation and reception of this interference of the State, it was seen that interests prevailed, varying the argumentative discourses, in order to brake the legal changes on the screen. Nevertheless, the Labor Accidents and Illnesses Act was finally approved in 1919, followed by the Eloy Chaves Law in 1923, and the Holiday Act in 1926. Lawyers at that time agreed with most of the normative content, as it is possible to verify in their works, but they wanted a more extensive intervention, even with conservative aims, maintainers of the social differences, but able to solve the class conflicts, what confirms the fit of the typology adopted. In this way, it was possible to see that, before Getúlio Vargas' project for the regulation of social issues, the molds were developed in the preceding decades, with the presence of the elements that would characterize our social protection system.